MAPPING MICRO AND SMALL INDUSTRY BASED ON RAW MATERIALS AND BUSINESS UNIT IN MERAUKE REGENCY WITH BIPLOT ANALYSYS - La Fajrin La Fajrin; Indah Ratih Anggriyani; Dariani Matualage; Fitryanti Pakiding (FMIPA Universitas Papua, 2022)
In the 2015-2035 national industrial development master plan, it is stated that micro and small industries are one of the contributors to the national economy. This means that the even distribution of industrial and regional development according to the potential of natural resources in each region is the main target. Merauke regency has the second largest number of micro and small industries in Papua Province. Business development in this industry was found to be difficult. Raw materials are one of the supporting factors in developing the micro and small industries business. The availability of sufficient and sustainable raw materials will facilitate production. The number of available business units also affects the absorption of labor. Increased employment can reduce unemployment and poverty rates. Information on the potential of raw materials and business units can be used as the basis for consideration of decisions, policies and efforts to increase the distribution of development and industrial estates according to the potential of natural resources. Biplot analysis was used in this study to map the potential raw materials for each district. This analysis describes summary table data in a two-dimensional graph, which is based on singular value decomposition. The results show that the first is the availability of raw materials for food crops which is high in the district of Jagebob, Kurik, Muting, Semangga and Ulilin. Animha and Naunkenjerai districts have high availability of raw materials for fishery commodities. The highest raw material for agricultural commodities is found in the Merauke district. Second is the number of business units for livestock and plant commodities, which is quite high in the Merauke district. The number of business unit for plantation commodities and services is quite high in the Kurik district. The number of service business unit is mostly found in Malind district. The resulting feasibility measure is 0.804 raw materials and 0.765 business units.